Advances in Targeted Therapy and Immunotherapy for Non-small Cell Lung Cancer Based on Accurate Molecular Typing - Dong, Jingsi; Li, Bingjie; Lin, Dan; Zhou, Qinghua; Huang, Depei (Frontiers in Pharmacology, 2019)
The essence of precision medicine is to achieve the goal of "individualized treatment" through genotyping of patients and targeted therapy. At present, the pathogenic genes of non-small cell lung cancer (NSCLC) have been studied most thoroughly and targeted therapy based on genotyping has been the most successful. This paper focuses on the precision treatment of NSCLC based on genotyping, comparing gene detection methods and summarize the latest progress of NSCLC immunotherapy.